Seasonal Evolution of Supraglacial Lakes on Baltoro Glacier From 2016 to 2020 - Wendleder, Anna; Schmitt, Andreas; Erbertseder, Thilo; D’Angelo, Pablo; Mayer, Christoph; Braun, Matthias H. (Frontiers in Earth Science, 2021)
The existence of supraglacial lakes influences debris-covered glaciers in two ways. Absorption of solar radiation in the water leads to a higher ice ablation, and water draining trough the glacier to the bed leads to a higher surface velocity. Rising air temperatures and changes in precipitation pattern provoke an increase of the supraglacial lakes in number and total area. Though, the seasonal evolution of the supraglacial lakes and thus their potential for influencing mass balance and ice dynamics has not yet been sufficiently analyzed. We present summer time series of supraglacial lake evolution on Baltoro Glacier in the Karakoram from 2016 to 2020. The dense time series is enabled by a multi-sensor and multi-temporal approach based on optical remote sensing data, namely Sentinel-2 and PlanetScope, and Synthetic Aperture Radar (SAR) remote sensing data, namely Sentinel-1 and TerraSAR-X. The mapping of the seasonal lake evolution uses a semi-automatic approach, which includes a Random Forest classifier applied separately on each sensor, harmonization of the SAR derived lake area to the optical area using a linear regression, and creation of a consistent time series of lake area using the Hausdorff distance. Seasonal variations are linked with the Standardized Precipitation Index (SPI) and Standardized Temperature Index (STI) based on air temperature and precipitation data of the climate reanalysis data set ERA5-Land. The largest lake area was found in 2018 with 5.783 km2, followed by 2019 with 4.703 km2, and 2020 with 4.606 km2. 2016 and 2017 showed the lowest areas with 3.606 km2 and 3.653 km2, respectively. A warmer spring (April-May) with higher precipitation rates leads to a higher formation of supraglacial lakes. A times series decomposition shows a linear increase of the lake area of 11.12 ± 9.57 % per year. Although the five-year observation period is too short to derive a significant trend with the given data variability, the tendency for a possible increase of the supraglacial lake area is in line with the pronounced positive anomalies of the SPI and STI during the observation period.